RANCANGAN PLTS ATAP/ROOFTOP(ON GRID) MENGGUNAKAN PVSYST DI SPN PASSO - Mahulette, Angela Carolina; Latupeirissa, Hamles L.; Parera, Lory Marcus (JURNAL SIMETRIK, 2025)
This study aims to design a rooftop Solar Power Plant (PLTS) system at the State Police School (SPN) Passo in Ambon using pvsyst software. This PLTS is designed with an on-grid system, connected to the PLN network, to utilize solar energy as a renewable energy source. The study began by collecting data on solar radiation intensity, daily energy consumption, and location characteristics such as roof area and orientation. This data was then processed using PVSyst to calculate the daily energy load, the required roof area, and the optimal solar panel capacity. The simulation results show that a PLTS system with a capacity of 41,27 kWp can meet the energy needs of SPN Passo, producing around 50,589 kWh per year with a Performance Ratio (PR) of around 80.87% This design is considered feasible with stable efficiency throughout the year, contributing to reducing energy consumption from PLN and supporting the use of environmentally friendly solar energy at SPN Passo. Keywords: PLTS ON GRID, Using PVSyst in SPN Passo